Terezijanski gozdni red za Kranjsko 1771 je mnogo več kot le predpis - Perko, Franc (Gozdarski vestnik, 2015)
This article shows problems at the emergence of the forest ordinance. An important part of the article deals with the analysis of the professional directions of forest ordinance, many of which are still relevant today, although they emerged 244 years ago. The article also shows comparisons of translations into Slovenian between 1849 and 1985 and thus displays the development of Slovenian professional forestry terminology.
Keywords: Terezijanski gozdni red za Kranjsko; gozdno načrtovanje; trajnost; trajnost donosa; obnova gozdov; nega gozdov; varstvo gozdov; proizvodna doba; gozdarska terminologija